Preparation method of polyvinyl alcohol-polyethylene glycol hydrogel film with low equilibrium swelling degree and high toughness

Through the multi-hydrogen bond cross-linking technology of PVA and PEG, the problem of difficult to prepare high-toughness hydrogel films with moderate thickness in the prior art is solved, and biosafe, simple and efficient preparation is achieved, and its application fields and multifunctions are expanded. sex.

CN119264485AActive Publication Date: 2025-01-07ANHUI PROVINCIAL SCI & TECH ACHIEVEMENTS TRANSFORMATION PROMOTION CENT (ANHUI PROVINCIAL INST OF SCI & TECH)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411551219.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The prior art lacks a simple, fast and gentle large-scale preparation process for the preparation of non-swelling or low-swelling high-toughness hydrogel films with moderate thickness, limiting the expansion of its application areas and the realization of versatility.

Method used

Using PVA and PEG as raw materials, low-equilibrium swelling and high-toughness hydrogel films are prepared at room temperature to 95 °C through multiple hydrogen bond crosslinking mechanism. Only a water bath pot, ordinary oven and stirring equipment are required to achieve biosafety and simple Efficient and large-scale production.

Benefits of technology

The prepared PVA-PEG hydrogel film has low swelling, high toughness and biosafety under swelling balance, and is easy to regulate thickness. It is suitable for multifunctional applications such as filtering filter membranes, sustained release materials and underwater conductive sensing. In the field, the preparation process is simple, time-consuming, non-toxic reagents, and the raw materials and equipment cost are low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264485A_ABST
    Figure CN119264485A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyvinyl alcohol-polyethylene glycol hydrogel film with low equilibrium swelling degree and high toughness. The preparation method comprises the following steps: adding PEG (Polyethylene Glycol) into a PVA (Polyvinyl Alcohol) aqueous solution, uniformly mixing at a high temperature under stirring, and carrying out ultrasonic defoaming, tape casting, drying and swelling treatment in the aqueous solution to prepare a finished product in one step. The prepared hydrogel film shows excellent performance combination, including thickness adjustability, low swelling property, high toughness and uniformity under swelling balance, and excellent acid and alkali resistance stability and biological safety. The method has the advantages of simple and fast preparation process, short time consumption (24 hours), no toxic reagent, no need of cross-linking agent, only use of three substances, harmlessness to human body, greenness, safety, low cost of raw materials, equipment and storage, easy regulation of the film thickness (0.2-0.7 mm), uniformity and flatness, and realization of large-scale and large-size production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel film preparation, and particularly relates to a method for preparing a PVA-PEG hydrogel film with low equilibrium swelling degree and high toughness. Background Art

[0002] The toughness of traditional hydrogel materials is often inversely proportional to the degree of swelling, and it is difficult to show excellent toughness at the same time in the swelling equilibrium state. However, hydrogels need to be used in liquid environments in most cases, and their swelling phenomenon is difficult to avoid, which will change the properties such as toughness and volume. Therefore, the study of low swelling or non-swelling high-strength and tough hydrogel technology has important scientific value and practical significance. In many published papers and patents, the prepared hydrogels are mostly three-dimensional, and there are fewer sheet-like hydrogel films. There are three main reasons: (1) The preparation of most hydrogels requires molds, but very thin parallel plate molds are not conducive to the gelation process and demolding; (2) The mechanical properties of hydrogels limit the formation of hydrogel films; (3) Many application scenarios require bulk hydrogels, and there is less demand for hydrogel films. However, compared with bulk hydrogels, hydrogel films have unique advantages in certain aspects. For example, because they are thinner, they have better interface adhesion, easier soft deformation, and more sensitive sensing ability, which makes them show unique application potential in the fields of flexible biosensors, wearable electronic devices, underwater conductive materials and drug sustained release carriers.

[0003] Patent CN108395549A discloses a high-strength, high-toughness antibacterial polyvinyl alcohol hydrogel and its preparation method, which is prepared from polyvinyl alcohol and tea polyphenols, and is gelled by a cross-linking mechanism that forms microcrystalline regions between PVA molecular chains through multiple freeze-thaw cycles. This method has a long preparation cycle and the hydrogel produced is a common shape, making it difficult to prepare a hydrogel film with uniform thickness in the micrometer to millimeter range.

[0004] Patent CN118126356A discloses a strong and transparent polyvinyl alcohol composite hydrogel and its preparation method, which comprises a polyvinyl alcohol aqueous solution and a cellulose nanofiber aqueous dispersion in a 60 Crosslinking and gelation under Coγ-ray or electron beam irradiation. This preparation method requires the use of high-energy rays that are less common and have safety risks.

[0005] Patent 105885064A discloses a toughened polyvinyl alcohol composite hydrogel and its application, using PVA and PEG aqueous solution or PVA and sodium alginate aqueous solution as liquid A, and boron compound aqueous solution as liquid B. Liquid A and liquid B are sprayed on the surface of an object at the same time in equal volumes, and a hydrogel can be quickly reacted to cover the surface of the object. The gelation mechanism of this hydrogel is chemical cross-linking. PEG, as a toughening substance, does not participate in the chemical cross-linking of the boron compound. This method of rapid cross-linking after spraying cannot well ensure the uniformity of cross-linking.

[0006] Patent CN118515902A discloses a strong and tough composite hydrogel film and its preparation and application, using polyvinyl alcohol and montmorillonite as component elements, glutaraldehyde / hydrochloric acid solution as a cross-linking agent, and preparing a hydrogel film with strong mechanical properties through evaporation self-assembly technology. The gelation mechanism of the hydrogel film in this invention is chemical cross-linking, and its preparation scheme uses toxic glutaraldehyde and hydrochloric acid, which is generally not suitable for certain biomedical fields.

[0007] Patent CN104151584B discloses a method for preparing an ultra-thin high-strength hydrogel film and its product. The preparation method first obtains a random copolymer solution A by polymerizing the monomers, and then drips A onto the surface of the poor solvent B of the random copolymer to obtain an ultra-thin high-strength hydrogel film. The gelation mechanism is the exchange of good solvent and poor solvent. The film has a breaking strength of 15 kPa~300 kPa, and the corresponding breaking elongation is 220%~120%. The film thickness obtained by this strategy of laying on the solvent surface is ultra-thin, 10~200 μ m. The preparation method of this patent is slightly complicated, and the water film that is too thin is too soft and difficult to achieve self-expansion out of water. It is easily damaged by external forces and is not convenient for practical application.

[0008] Patent CN116410501A discloses a method for preparing an ultra-thin high-strength hydrogel film, which requires the use of four substances: a film former, a modifier, an anti-gelling agent, and a pore former. The prepared sol-gel solution is scraped on a purified and hydroxylated base film, and then dried and soaked to obtain an ultra-thin high-strength hydrogel film. The preparation method does not require large instruments and equipment. In this patent, PVA can be a film former, and PEG can be a pore former and an anti-gelling agent. However, a modifier must be added and the base film must be cleaned and hydroxylated. The film thickness is 20 to 150 μ m, 4 to 6 types of raw materials are used, and there are slightly more steps.

[0009] In summary, there is currently a lack of a simple, rapid, and gentle large-scale preparation process that uses biosafe raw materials, as few raw material types as possible, and a moderate thickness (greater than 200 μm, less than 1 mm), which greatly limits the expansion of its application fields and the realization of multifunctionality. Summary of the invention

[0010] In view of the shortcomings of the above-mentioned prior art, the present invention provides a method for preparing a PVA-PEG hydrogel film with low equilibrium swelling and high toughness. The hydrogel film of the present invention uses PVA and PEG as raw materials, is formed by a multiple hydrogen bond cross-linking mechanism, has low equilibrium swelling and high toughness under swelling equilibrium, is biosafe, has a mild, simple and efficient preparation method, and can be mass-produced in large sizes.

[0011] The present invention uses only three biosafe substances, PVA, PEG and water, as raw materials, and prepares a hydrogel film with low equilibrium swelling degree, high toughness and easily adjustable thickness at room temperature to 95°C through a multiple hydrogen bond cross-linking mechanism. The preparation method is gentle, simple and efficient, and can be mass-produced in large sizes. It only requires a water bath, an ordinary oven and stirring equipment, and is easy to industrialize.

[0012] The method for preparing a low equilibrium swelling degree and high toughness PVA-PEG hydrogel film of the present invention comprises the following steps: At room temperature, liquid low molecular weight PEG or high molecular weight PEG aqueous solution is added to the PVA aqueous solution, and the mixture is heated at high temperature and stirred to obtain a casting mixture, ultrasonic degassing, cast, and after drying, the film is immersed in a solvent to swell, thereby obtaining a low swelling and high toughness PVA-PEG hydrogel film.

[0013] The PVA aqueous solution is obtained by dissolving a solid PVA raw material in water at 85-95° C. under stirring. The mass concentration of the PVA aqueous solution is 2-12 wt %.

[0014] The relative molecular mass of the PVA is 60,000 to 200,000.

[0015] The low molecular weight PEG in liquid form at room temperature refers to PEG100, PEG200, PEG400, PEG600, etc. with relatively small molecular weight, which can be directly added to the PVA aqueous solution or prepared into a PEG aqueous solution before being added to the aqueous solution; the high molecular weight PEG refers to PGE800, PEG1000, PEG2000, PEG4000, PEG6000, PEG8000, PEG10000, etc. which are solid at room temperature, which are prepared into corresponding aqueous solutions and then added to the PVA aqueous solution; the concentration of the PEG aqueous solution is related to its own solubility, and the PEG with small molecular weight that is liquid at room temperature can be directly added, and the high molecular weight PEG can be prepared into a 1-60 wt% aqueous solution and added.

[0016] The mass ratio of the solute PVA and PEG in the hydrogel film is 1:0.5-3.0.

[0017] Furthermore, the high temperature and mixing heating refers to heating the prepared PVA-PEG aqueous solution at room temperature to 80°C and stirring and mixing to fully destroy the local high-concentration hydrogen bonds and make the PVA and PEG molecular chains evenly dispersed. The higher the temperature, the better the mixing effect. However, when adding low molecular weight PEG or its aqueous solution to an aqueous solution with a low mass concentration of PVA, it can also be stirred and mixed at room temperature, and the prepared film has good uniformity.

[0018] The tape casting is to spread the mixed film casting mixture in a flat bottom container, and control the amount of the film casting mixture to be 0.16-0.56 g / cm 2 The final film thickness can be controlled by adjusting the height of the casting mixture and / or the mass fraction of PVA plus PEG solute. The thickness of the low swelling and high toughness PVA-PEG hydrogel film prepared by the present invention is 0.2-0.7 mm.

[0019] The drying can be carried out at room temperature or under heated blast. When drying under heated blast, the temperature is between 25°C and 60°C. The higher the temperature, the shorter the time required to complete the drying. The time required to complete the drying is also related to the mass of the casting liquid per unit area.

[0020] The solvent used for the swelling is water.

[0021] The cross-linking mechanism of PVA-PEG hydrogel film of the present invention is the multiple hydrogen bond interactions between PVA and PEG. These two macromolecules only contain three kinds of elements of C, H and O, and the structural units are consistent, all of which are -(C2H4O)-. In PVA, O is located on the side chain hydroxyl group, and in PEG, O is located on the main chain. Such O element distribution makes the widely existing hydrogen bonds between these two macromolecules anchor each other, and is not easy to dissociate, thereby showing a low affinity to free small molecule water. Because of this, the equilibrium swelling degree of this hydrogel film is low, the toughness is high, there is no biological toxicity, and the acid and alkali resistance stability is good.

[0022] The cross-linking system of PVA-PEG of the present invention is special, which is derived from the similarity of the molecular structures of the two. The key to forming cross-linking is that the mass ratio of the two polymers in the casting solution is PVA:PEG=1:0.5~3, and the PEG content is high under this ratio. If the PVA-PEG hydrogel film is dried, the mass fraction of PEG can reach 30~75 wt%. The high PEG ratio is a key factor to ensure that the PVA and PEG aqueous solutions can be evaporated and dried at room temperature (drying at high temperature is to shorten the film making cycle) to form a film. The appropriate mass ratio of PVA to PEG can ensure the formation of multi-point cross-linking, and these cross-linking points are anchored to each other, thereby reducing the hydrogen bonding points between the polymer and water.

[0023] The preparation method of the low equilibrium swelling degree and high toughness PVA-PEG hydrogel film of the present invention comprises the following specific steps: (1) Prepare a PVA aqueous solution with a mass fraction of 2-12 wt%.

[0024] (2) Adding an aqueous solution of a low molecular weight PEG which is liquid at room temperature or a high molecular weight PEG which is solid at room temperature to the above PVA aqueous solution, wherein the concentration of the aqueous solution is 1 to 60 wt %, to obtain a casting mixture.

[0025] (3) The above-mentioned casting mixture is fully mixed under heating and stirring, and the heating temperature is room temperature to 80°C.

[0026] (4) Degas the mixed film casting mixture by ultrasonic treatment.

[0027] (5) Cast the mixed film casting mixture into a flat-bottomed container.

[0028] (6) The casting film mixture cast in the flat-bottom container is dried at room temperature or under heating and blowing, wherein the temperature is 25-60°C under heating and blowing to obtain a dry film.

[0029] (7) The dried film is immersed in water until equilibrium swelling occurs, thereby obtaining a low swelling and high toughness PVA-PEG hydrogel film.

[0030] The mixing operation is performed during and / or after adding other raw materials or raw material solutions to the polymer aqueous solution, and can be one or more of mechanical stirring, stirring, shaking, ultrasound, and heating.

[0031] The low swelling and high toughness PVA-PEG hydrogel film prepared by the present invention has low swelling, high toughness under swelling equilibrium, and biological safety. Unless otherwise specified, the PVA-PEG hydrogel film and performance data in the present invention are all samples under swelling equilibrium in water, not samples after drying and then swelling equilibrium, and the PEG used is PEG1000 with a molecular weight of 1000.

[0032] Patent CN118240245A discloses a chitosan-polyvinyl alcohol-tannic acid cross-linked network hydrogel and its preparation method and application, wherein tannic acid with multiple phenolic hydroxyl groups acts as a small molecule cross-linking agent. The purpose of the invention is to prepare a body-shaped hydrogel material, and a freeze-drying step is used in the preparation process, which prolongs the material preparation cycle.

[0033] Patent CN115570859B discloses a recyclable high-strength and tough composite hydrogel, which is prepared by inorganic ion polymerization and self-assembly to prepare a composite film, and then directional stretching and layer-by-layer bonding stacking to prepare a composite hydrogel. The purpose of this invention is also to prepare a high-strength and tough body material. The gelation mechanism is ionic cross-linking, with slightly more preparation steps and a longer cycle.

[0034] Patent CN115850745B discloses a method for preparing a natural polymer hydrogel film, its products and applications, wherein a dilute acetic acid aqueous solution of chondroitin sulfate and chitosan is simultaneously added dropwise to a dilute acetic acid aqueous solution to obtain a milky suspension solution, and then the suspension solution is vacuum dried and soaked to swell to obtain a hydrogel film, which can be used as an anti-adhesion diaphragm for uterine cavity, and the gelation mechanism is the electrostatic interaction between positive and negative charges. The in vivo degradation period of the sample is 7 to 14 days. The raw materials and gelation mechanism used in the patent are different from those of the present invention.

[0035] Patent CN108066819B discloses a high-strength natural polymer hydrogel film and its preparation method, which is cross-linked by carrageenan and chitosan through ionic bonds and hydrogen bonds. The film-forming liquid is also poured into a flat-bottomed container, dried and soaked in water to swell to swelling equilibrium. The maximum elongation at break of the obtained hydrogel film is not less than 120%, and the maximum breaking stress is not less than 6.7 MPa. The casting, drying and swelling steps of the film in the present invention are consistent with this, but the raw material category is completely different from the above patent, and the gelation mechanism of the hydrogel film in the present invention also only contains hydrogen bonding. The minimum elongation at break of the obtained hydrogel film is not less than 350%, and the deformation capacity is somewhat different.

[0036] The low swelling and high toughness PVA-PEG hydrogel film prepared by the present invention can be added with other functional substances such as drugs, fertilizers, conductive substances, etc. during the preparation process, and the corresponding functional film can be used in the fields of filtration membranes, sustained-release materials, underwater conductivity, and underwater sensing.

[0037] The preparation process of the hydrogel film of the present invention is simple, time-consuming (24 h), does not contain toxic reagents, does not require cross-linking agents, and only uses three substances, all of which are harmless to the human body, green and safe, and the cost of raw materials, equipment and storage is low. The film prepared by the existing preparation process is relatively thin at 20~150 μ m (poor solvent surface laying method, it is difficult to prepare a film with a larger thickness). Thickness less than 200 μ The hydrogel film of 0.1 mm spontaneously aggregates into bundles when out of water, cannot spread itself, and is difficult to apply. The film thickness of the present invention is 0.2-0.7 mm, is easy to control, is uniform and flat, and can be mass-produced in large sizes.

[0038] The low swelling and high toughness PVA-PEG hydrogel film prepared by the present invention is formed by multiple hydrogen bond cross-linking, and has low equilibrium swelling degree (the water content of the original film is 93±0.9%, the equilibrium swelling degree is 14.3±0.9; the equilibrium swelling degree of the film after drying once is 3.2±0.7), high toughness (0.5~1.1 MJ / m 3 )、High fracture energy(0.8~2.8 KJ / m 2 ), elongation at break of 350%~460%, breaking strength of 300~700 kPa, good biosafety, mild preparation conditions, simple method, large-scale production (30 cm × 50 cm or larger, depending on the size of the flat-bottomed container), low cost of raw materials, equipment and storage. The thickness, cross-linking density, swelling and toughness of the film are easy to adjust. The membrane material itself can be embedded with a variety of functional materials. It can be used for water filtration membrane materials, drugs, fertilizer slow-release materials, underwater conductivity and underwater sensing, with good economic benefits and commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The photo and flexibility display of the PVA-PEG hydrogel film prepared in Example 1 of the present invention.

[0040] Figure 2 This is a large-sized 30 cm × 50 cm PVA-PEG hydrogel film prepared in Example 1 of the present invention.

[0041] Figure 3 The PVA-PEG hydrogel films of different thicknesses prepared in Example 1 of the present invention.

[0042] Figure 4 This is the PVA-PEG (PEG4000) hydrogel film prepared in Example 7 of the present invention.

[0043] Figure 5 The PVA-CMCNa hydrogel film prepared in Example 8 of the present invention: (a) macroscopic photos of PVA-CMCNa hydrogel films with three different component ratios, (b) photos of the PVA-CMCNa hydrogel film spontaneously aggregating into bundles after leaving water.

[0044] Figure 6 The PVA-maltodextrin hydrogel film prepared in Example 9 of the present invention: (a) a macroscopic photograph of the PVA-maltodextrin hydrogel film, and (b) a photograph of the PVA-maltodextrin hydrogel film spontaneously aggregating into bundles after being separated from water.

[0045] Figure 7 Schematic diagram of the widely existing mutually anchoring hydrogen bonding interactions between PVA and PEG in the PVA-PEG hydrogel film prepared in Example 1 of the present invention.

[0046] Figure 8 This is a SEM image of the surface of the PVA-PEG hydrogel film prepared in Example 1 of the present invention.

[0047] Fig. 9 The thermal stability of the PVA-PEG hydrogel film prepared in Example 1 of the present invention is demonstrated.

[0048] Fig.10 The acid and alkali resistance of the PVA-PEG hydrogel film prepared in Example 1 of the present invention after being immersed in different pH environments for 14 days is demonstrated.

[0049] Fig.11 These are photos of the PVA-PEG hydrogel film prepared in Example 1 of the present invention being able to withstand twisting, knotting and hand-held stretching.

[0050] Fig.12 The tensile stress-strain curves of the PVA-PEG hydrogel films of different thicknesses prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0051] In order to further understand the present invention, the following is a detailed description of a low swelling and high toughness PVA-PEG hydrogel film provided by the present invention and its preparation method and basic properties in conjunction with the embodiments, but the present invention is not limited to these embodiments. Non-essential changes made by skilled technicians in this field under the guidance of the core idea of ​​the present invention still fall within the scope of protection of the present invention.

[0052] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used. Embodiment 1:

[0053] Prepare a 5 wt% PVA (1799) aqueous solution and a 50 wt% PEG (PEG1000, M w =1000) aqueous solution, add 2.5 g of PEG aqueous solution to 10 g of PVA aqueous solution under mechanical stirring to obtain a casting mixture, place it at a constant temperature of 40 ° C for 1 h, and lay it in a flat-bottomed container by casting. The amount of the casting mixture is controlled to be 0.16 g / cm 2 , and placed in a 40℃ forced air oven. Dry for 12 hours to obtain a dry film. The dry film is translucent. Soak it in a large amount of water to obtain a PVA-PEG hydrogel film. The preparation cycle is 24 hours. The photos and flexibility of the PVA-PEG hydrogel film are shown in Figure 1 The same method was used to prepare a large-size 30 cm × 50 cm PVA-PEG hydrogel film, see Figure 2 . Embodiment 2:

[0054] The difference from Example 1 is that the amount of the casting mixture is controlled to be 0.24 g / cm 2 , the rest of the content is consistent with Example 1. Embodiment 3:

[0055] The difference from Example 1 is that the amount of the casting mixture is controlled to be 0.24 g / cm 2 , the rest of the content is consistent with Example 1. Embodiment 4:

[0056] The difference from Example 1 is that the amount of the casting mixture is controlled to be 0.32 g / cm 2 , the rest of the content is consistent with Example 1. Embodiment 5:

[0057] The difference from Example 1 is that the amount of the casting mixture is controlled to be 0.40 g / cm 2 The rest of the contents are consistent with Example 1. The photos of the PVA-PEG hydrogel films of different thicknesses prepared in Examples 2, 3, and 4 are shown in the attached Figure 3 . Embodiment 6:

[0058] The difference from Example 1 is that when drying, it is left open at room temperature, and a dry film can be obtained after 3 days, and then soaked in a large amount of water to obtain a PVA-PEG hydrogel film. The preparation cycle is 3 days. Embodiment 7:

[0059] Prepare a 5 wt% PVA (1799) aqueous solution and a 50 wt% PEG (PEG4000, M w =4000) aqueous solution, 0.9 g of PEG aqueous solution was added to 10 g of PVA aqueous solution under mechanical stirring to obtain a casting mixture, which was kept at 70 °C for 1 h and laid in a flat-bottomed container by tape casting. The amount of the casting mixture was controlled to be 0.32 g / cm 2 , and placed in a 60℃ forced air oven. Dry for 12 hours to obtain a dry film. The dry film is translucent. Soak it in a large amount of water to obtain a PVA-PEG supramolecular hydrogel film. The preparation cycle is 24 hours. The prepared PVA-PEG (PEG4000) hydrogel film is similar to PVA-PEG (PEG1000) and has good uniformity. The thickness and macroscopic photos are shown in Figure 4 . Embodiment 8:

[0060] This example is a counter-proof experiment to assist in verifying the cross-linking mechanism of PVA-PEG hydrogel film. Prepare a 5 wt% PVA (1799 type) aqueous solution, prepare a 0.1 wt% sodium carboxymethyl cellulose (CMCNa) aqueous solution, add 2.0 g, 3.0 g, and 4.0 g of CMCNa aqueous solution to 10 g of PVA aqueous solution under mechanical stirring to obtain a homogeneous film casting mixture, place it at a constant temperature of 70°C for 1 h, and lay it in a flat-bottomed container by tape casting. The amount of the film casting mixture is controlled to be 0.24 g / cm 2 , placed in a 60℃ forced air oven, and dried for 12 hours to obtain a dry film. The dry film is colorless and transparent, and is easy to break. After soaking in a large amount of water, only a very thin flexible film remains within 5 minutes. After soaking for 48 hours, it is observed that the film does not dissolve, but has almost no mechanical properties. It gathers into bundles when it is out of water. Figure 5 . Embodiment 9:

[0061] This example is also a counter-proof experiment to assist in verifying the cross-linking mechanism of PVA-PEG hydrogel film. Prepare a 5 wt% PVA (1799 type) aqueous solution, prepare a 10 wt% maltodextrin aqueous solution, add 7.0 g of maltodextrin aqueous solution to 10 g of PVA aqueous solution under mechanical stirring to obtain a homogeneous film casting mixture, place it at a constant temperature of 70°C for 1 h, and lay it in a flat-bottomed container by tape casting. The amount of the film casting mixture is controlled to be 0.24 g / cm 2 , placed in a 60℃ forced air oven, and dried for 12 hours to obtain a dry film. The dry film is colorless and transparent, and is easy to break. After soaking in a large amount of water, only a very thin flexible film remains within 5 minutes. After soaking for 48 hours, it is observed that the film does not dissolve, but has almost no mechanical properties. It gathers into bundles when it is out of water. Figure 6 . Comparative Example 1:

[0062] The difference from Example 1 is that no PEG is added, only a PVA aqueous solution is used, and the dried PVA film finally obtained will dissolve in water without forming a hydrogel. Performance Test 1:

[0063] The swelling properties of the PVA-PEG hydrogel film prepared in Example 1 were tested, and the results showed that the water content of the original film was 93±0.9%, and the equilibrium swelling degree was 14.3±0.9; after drying once, the equilibrium swelling degree of the film was 3.2±0.7. The reason why the PVA-PEG hydrogel film has low swelling properties is that both PVA and PEG contain only three elements, C, H, and O, and the structural units are consistent, all -(C2H4O)-, and the mass ratio of PVA to PEG is appropriate (PVA:PEG=1:0.5~3.0). Among them, the O of PVA exists in the side chain in the form of hydroxyl, which is more flexible, and the O on PEG is on the main chain, which is limited in flexibility. Such O element distribution and the appropriate ratio between the two make the widely existing hydrogen bonds between the two polymers anchor each other and are not easy to dissociate, thereby showing low affinity to free small molecule water, that is, low swelling. Figure 7 Schematic diagram of the extensive multiple hydrogen bond cross-linking between PVA and PEG. It has to be said that this diagram does not combine the actual molecular bond length (in PVA and PEG, the CC bond length is about 0.15 nm, the CO bond length is about 0.14 nm, the CH bond length is about 0.11 nm, and the OH bond length is about 0.096 nm) and configuration information very well, but it also reflects the interaction hypothesis of extensive cross-linking and mutual anchoring by hydrogen bonds. In order to further support this hypothesis, the inventors also designed a counter-proof experiment. PVA and sodium carboxymethyl cellulose (chemical formula [C6H7O2(OH)2OCH2COONa] n ) mixed solution (Example 8), PVA and maltodextrin (chemical formula (C6H 10 O5) n ) mixed solution (Example 9), without exception, the prepared membranes were mostly dissolved in water, and the thickness of the prepared membranes was very thin, much less than the expected thickness of the feed. This shows that extensive multiple hydrogen bonds cannot be formed between PVA and the polysaccharide structure, because there are fewer sites for hydrogen bond interaction between the polysaccharide structure and the PVA structure, and it is not easy to form a mutual anchoring relationship, so the degree of cross-linking is weak. Performance Test 2:

[0064] The microstructure of the PVA-PEG hydrogel film prepared in Example 1 was tested, and the results are shown in Figure 8 , the surface of the film is smooth and dense. Performance Test 3:

[0065] The thermal stability of the PVA-PEG hydrogel film prepared in Example 1 was tested. Fig. 9The results showed that the PVA-PEG hydrogel film could remain stable for a long time (tested for 24 h) at 50°C, but when the temperature was higher than 60°C, it became soft, thin and deformed, indicating that at this temperature, the hydrogen bond cross-linking effect of the PVA hydrogel film began to be significantly destroyed. Performance Test 4:

[0066] The acid and alkali resistance of the PVA-PEG hydrogel film prepared in Example 1 was tested by soaking it in pH = 1 (0.1 mol / L HCl aqueous solution), pH = 7 (ultrapure water) and pH = 13 (0.1 mol / L NaOH aqueous solution) for 14 days, and comparing the swelling before and after soaking. Fig.10 The results showed that there was no difference in the hydrogel films immersed in solutions with pH = 1, 7, and 13 for 14 days, indicating that the hydrogen bond cross-linking mechanism was not greatly affected by pH, and the PVA hydrogel film had excellent acid and alkali resistance. Performance Test 5:

[0067] The mechanical properties of the PVA-PEG hydrogel film prepared in Example 1 were tested by hand-held twisting, knotting and stretching. Fig.11 The results show that the PVA-PEG hydrogel film can withstand ordinary deformation and rapid recovery. Further, the above samples (the prepared film samples with a water content of 93±0.9%, the samples in the swelling equilibrium state, not the samples after drying and re-swelling) were subjected to a tensile test at a rate of 50 mm / min. Fig.12 The results showed that the modulus of PVA-PEG hydrogel films of different thicknesses was 50~180 kPa, the elongation at break was 350%~460%, the breaking strength was 300~700 kPa, and the toughness was 0.5~1.1 MJ / m 3 , fracture energy is 0.8~2.8 kJ / m 2 , showing high toughness under excellent swelling balance. Performance Test 6:

[0068] The biosafety of the PVA-PEG hydrogel film prepared in Example 1 was tested and evaluated by a fertilized zebrafish egg hatching experiment. The experimental group was hatched in pure water containing the PVA-PEG hydrogel film. Five groups were set up in the experiment. Each group initially used 30 eggs. The hatching conditions after 3 days were 27, 27, 28, 24, and 23 live fry, respectively. The control group was hatched in pure water. Four groups were set up in the experiment. Each group initially used 30 eggs. The hatching conditions after 3 days were 27, 24, 29, and 30 live fry, respectively. The statistical significance test level between the two groups of data was p=0.32, p≥0.05, indicating that there was no obvious difference in the experimental results of the two groups, indicating that the presence of the PVA-PEG hydrogel film did not affect the hatching of zebrafish eggs, and the biosafety was good.

Claims

1. A method for preparing a low equilibrium swelling ratio and high toughness PVA-PEG hydrogel film, characterized in that The steps include: At room temperature, liquid low molecular weight PEG or high molecular weight PEG aqueous solution is added to the PVA aqueous solution, and the mixture is heated at high temperature and stirred to obtain a casting mixture, ultrasonic degassing, cast, and after drying, the film is immersed in a solvent to swell, thereby obtaining a low swelling and high toughness PVA-PEG hydrogel film.

2. The preparation method according to claim 1, characterized in that: The PVA aqueous solution is obtained by dissolving a solid PVA raw material in water at 85-95° C. under stirring, and the mass concentration of the PVA aqueous solution is 2-12 wt %.

3. The preparation method according to claim 2, characterized in that: The relative molecular mass of the PVA is 60,000 to 200,000.

4. The preparation method according to claim 1, characterized in that: The low molecular weight PEG is selected from one or more of PEG100-PEG600; the high molecular weight PEG is selected from one or more of PEG800-PEG10000.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the solute PVA and PEG in the hydrogel film is 1:0.5-3.

0.

6. The preparation method according to claim 1, characterized in that: The tape casting is to spread the mixed film casting mixture in a flat bottom container, and control the amount of the film casting mixture to be 0.16-0.56 g / cm 2 The final film thickness can be controlled by adjusting the height of the casting mixture and / or the mass fraction of PVA plus PEG solute.

7. The preparation method according to claim 6, characterized in that: The thickness of the prepared PVA-PEG hydrogel film is 0.2~0.7 mm.

8. The preparation method according to claim 1, characterized in that: The solvent used for swelling is water.

Citation Information

Patent Citations

  • Preparation method of polyvinyl alcohol composite hydrogel with fast hydroscopicity, high swellbility and adjustable aperture sizes

    CN105295075A

  • Polyvinyl alcohol film with high swelling degree and preparation method thereof

    CN105924866A

  • Glycerin modified polyvinyl alcohol hydrogel as well as preparation method and application thereof

    CN115232330A

  • Thermally conductive polymers and methods for making

    US20190010322A1